Proof: Get Begin Expr State 3
Let's prove the following theorem:
if the following are true:
- the expression at time 3 = 1
- expression state at time 3 = "begin_expr"
- 1 is constant
- parent stack at time 3 = [
__eq__(1, 3)
, [ ] ]
then expression state at time 4 = "return"
Proof:
Given
1 | the expression at time 3 = 1 |
---|---|
2 | expression state at time 3 = "begin_expr" |
3 | 1 is constant |
4 | parent stack at time 3 = [ __eq__(1, 3) , [ ] ] |
# | Claim | Reason |
---|---|---|
1 | expression state at time (3 + 1) = "return" | if expression state at time 3 = "begin_expr" and the expression at time 3 = 1 and 1 is constant and parent stack at time 3 = [ __eq__(1, 3) , [ ] ], then expression state at time (3 + 1) = "return" |
2 | 3 + 1 = 4 | 3 + 1 = 4 |
3 | expression state at time (3 + 1) = expression state at time 4 | if 3 + 1 = 4, then expression state at time (3 + 1) = expression state at time 4 |
4 | expression state at time 4 = "return" | if expression state at time (3 + 1) = expression state at time 4 and expression state at time (3 + 1) = "return", then expression state at time 4 = "return" |
Comments
Please log in to add comments